OPTIMASI PRODUKSI PADA MATURE FIELD: SCREENING KANDIDAT SUMUR UNTUK STIMULASI HYDRAULIC FRACTURING - Fahreza Nurwafa, Alvin
Currently, oil production in Indonesia continues to decline because many fields have passed their peak production due to many wells are idle or have low rates. In this condition, it requires a method to increase oil production to meet national energy needs. The method is well stimulation, one of which uses hydraulic fracturing. However, selection is needed to select well candidates that can be stimulated due to high operating costs to maximize production. The study was conducted on the Y field which is an oil field with sandstone formation with a total of 30 wells. The selection of well candidates was conducted using the heterogeneity index method using production data, determination of recoverable reserves with decline curve analysis and cum-cum plot, identification of well data such as permeability and skin, and well performance evaluation analysis using Pudjo Sukarno IPR (1986). From a total of 30 wells, 2 well candidates for hydraulic fracturing stimulation were obtained. The stimulation candidate wells are TM-20 and TM-25. Hydraulic fracturing stimulation was performed on both wells using PKN and KGD models. The KGD model showed the highest increase in flow rate with a fracture length for TM-20 of 200 ft, a fracture height of 42 ft, and a fracture width of 0.205 in., while for TM-25 the fracture length was 250 ft, a fracture height of 34 ft, and a fracture width of 0.242 in. With this geometry model, the AOF oil for TM-20 is 63.7 STB/day and TM-25 is 264.1 STB/day. The study shows that screening and optimization can improve the production of wells in the old field.